PERBANDINGAN KINERJA BANK DEVISA DAN BANK NON DEVISA DI INDONESIA (Students' Journal of Accounting and Banking, 2012)
This studyaims to determine whether there are significant differencesbetween Bank bank Non Foreign Exchange Foreign exchange with theuse of financial ratio analysi and statistical analysis. Financial ratio analysisusing theReturnon Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), and the Loan to Deposit Ratio (LDR).While the statistic alanalys is using two different test average (independent sample t-test). The data used as research material is secondary data from financial statements obtained from Bank Indonesia during the period 2006-2009.The result isno significant difference between Bank Bank Non Foreign Exchange Foreign Exchange with during the period 2006-2009 when measured using ther atio of LDR and ROA, butthe ratio of ROE and BOPO there are significant differencesbetween Bank Bank Non Foreign Exchange and Foreign Exchange during the period 2006-2009.Where is the profitability ratio is representedby ROA,ROE, and BOPO. While liquidity ratios are representedby the LDR. Forfur ther study when taking the title or the same topic and use this study as a referenceit is advisable to add financial ratio stestedor seekcomparable periodsbefore and after the crisis and before and after or apolicy that affects the macro toget the results moreaccurate.Keywords: Performance compar is on Bank BUSN Non Foreign Exchange and Foreign Exchange, LDR, ROA, ROE,